Strategi Komunikasi Konsep “Bayar Seikhlasnya” di Kafe X - Rheza Erwin Ismail; Tresna Wiwitan (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Competition in the business world, especially in the culinary field, is currently experiencing an increasing level of competition, namely a condition that includes price and quality factors. Economic growth is experienced by many big cities in Indonesia, one of which is Bandung. This study aims 1) to analyze the communication strategy planning of the concept of